IMPLEMENTASI METODE EDUTAINMENT UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA BERBANTUAN MEDIA MONOPOLI DI SEKOLAH DASAR - Saragih, Christin Natalia; Sinaga, Reflina; Tanjung, Darinda Sofia; Gaol, Rumiris Lumban; Abi, Antonius Remigius (Universitas Negeri Medan, 2024)
The results of this research indicate an increase in student learning outcomes in class IV mathematics lessons at SD Negeri 097802 Tumbukan Dalig, Simalungun Regency. This is proven by the results of research on the pretest (initial test) where 6 students (31.57%) got a complete score, while 13 students (68.42%) got an incomplete score, with an average learning result of 59.15. In the first cycle posttest, it increased to 11 students (57.89%) who completed while 8 students (42.10%) did not, with an average learning outcome of 66.73. In the second cycle posttest, completeness of learning outcomes increased to 16 students (84.21%) who completed and 3 students (15.78%) received an incomplete score, with an average learning outcome of 75.78. Furthermore, from the results of observations of teacher activities in implementing cycle I learning, an average of 52% (sufficient) was obtained and observations of student activities were obtained with an average of 50 (sufficient). In cycle II the results of teacher observations increased to 84% (very good) and the results of observations of student activities also increased to 86 (very good) thus it was found that by implementing the edutainment method there was an increase in the learning outcomes of class IV students at SD Negeri 097802 Tumbukan Dalig , Simalungun Regency.